The Effect of Receivable Turnover and Inventories Towards Liquidity of Cigarette Industries - Rika Amalia; Alin Agustina; Zahra Prathamy; Irwan Hermawan (Westscience Press, 2023)
The purpose of this study was to investigate the influence of accounts receivable and inventory turnover on the liquidity of firms in the tobacco sub-sector listed on the IDX from 2017 to 2019. The study employs quantitative methodologies, including secondary data from financial statements, papers, journal articles, and three example firms. The firms analyzed are those in the tobacco sector listed on the Indonesian Stock Exchange and publish annual financial reports in both Rupiah and millions. Divide net sales by average accounts receivable to determine accounts receivable turnover. Inventories turnover is defined as the ratio of sales to average inventory. Liquidity is determined using the quick ratio, computed as the product of current assets and current liabilities. The results indicated that accounts receivable turnover had no meaningful influence on liquidity when considered concurrently and partly. Inventory turnover, whether it occurs concurrently or in stages, has a substantial impact on liquidity.